IMPERATIF DESAKAN DALAM BAHASA BANJAR DI PASAR TRADISIONAL HULU SUNGAI - Rissari Yayuk (Multilingual, 2015)
This study examines the issue form and pragmatic strategies of the imperativeinsistence in Banjar language. Through this study will be known speaking cultures of Banjar sosciety. The research objective was to describe the nature and pragmatic strategies of imperative in Banjar language. The method useisdescriptive qualitative by using record and field-notes techniques. The data werecollected from daily speech events in the traditional markets in the Wujud District at the South, North, and Central upstream. The data collected from January until March 2015. The result of the research that is pragmatic imperative insistence in the speech between sellers and buyers at the upstream traditional market in South Kalimantan is using markers, such as: ayu 'come on', kasi/capati/lajui 'quickly', the affirming gin 'yes', and the reason larangnya'expensive'. Besides, the other marker is when the speaker uses utter speech intonation hard or firm. The sentence use is a command line mode while the narrative strategies used in the imperative command of Banjar language is direct strategy.